A high-temperature starch-type sizing agent for electronic-grade glass fiber yarn, and preparation method, product and application thereof

Through the use of high-temperature starch-type wetting agents, the problems of high consumption of wetting agents, many hairs and poor wear resistance in the production of D450 and D900 electronic-grade glass fiber yarns are solved, and efficient production of yarns and excellent weaving performance are achieved.

CN117486504BActive Publication Date: 2025-01-07JUSHI GRP CO

Patent Information

Application Number
CN202311438401.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-01
Publication Date
2025-01-07
Estimated Expiration
2043-11-01

AI Technical Summary

Technical Problem

The prior art is difficult to effectively solve the problems of high wetting agent consumption, many hairs, poor wear resistance, strict production environment requirements, low production efficiency and many defects on the fabric in the production of D450 and D900 electronic grade glass fiber yarns.

Method used

Provide a high temperature starch type wetting agent containing a mixture of high linear corn starch, acrylamide graft modified starch and acetyl modified starch, combined with pretreatment agent, grease, emulsifier and antistatic agent, through ultrafine pulverization and high pressure Steaming and cooking treatment improves the bundling and wear resistance of the yarn.

Benefits of technology

It significantly reduces the yarn's broken head rate and hair ratio, reduces the amount of powder falling from the woven fabric, improves the wear resistance and weaving performance of the yarn, reduces the defects on the fabric, and improves the production efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FHA0000007471850000011
    Figure FHA0000007471850000011
  • Figure FHA0000007471850000021
    Figure FHA0000007471850000021
  • Figure GHA0000007471860000021
    Figure GHA0000007471860000021
Patent Text Reader

Abstract

The present application discloses a high-temperature starch-type sizing agent for electronic-grade glass fiber yarn, which is an aqueous solution of effective ingredients, the solid content of the sizing agent is 5.19-10.76%, and the solid mass of each effective ingredient accounts for the percentage of the total solid mass of the sizing agent: starch 3.40-7.00%; oil 1.10-2.30%; emulsifier 0.05-0.10%; pretreatment agent A 0.15-0.40%, pretreatment agent B 0.30-0.50%; antistatic agent 0.17-0.40%; ammonia water 0.02-0.06%. The starch is a mixture of high-amylose corn starch, acrylamide grafted modified starch and acetyl modified starch, and the mass ratio of the three is 1:1:1-5:2:1. This wetting agent can maintain the advantages of high-temperature system wetting agents in terms of high yarn bundling and good covering properties, while reducing yarn stiffness and improving yarn lubricity, making it less likely for D450 and D900 yarns to produce loose fibers during the production process, reducing the impact of production process fluctuations on yarn quality, significantly improving yarn weaving performance, and significantly reducing fabric defects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of glass fiber surface treatment agents, and in particular to the technical field of production of sizing agents for electronic grade glass fibers. Specifically, the present application relates to a high-temperature starch-type sizing agent for D450 and D900 electronic grade glass fiber yarns, and a preparation method, product and application thereof. Background Art

[0002] With the revolution of information technology, digital power has gradually entered the stage of high-speed information processing and high-frequency signal transmission. In order to process the increasing data, the frequency of electronic equipment has become higher and higher, and electronic products have been developing in the direction of light, thin and small. High-density interconnection (HDI) technology has also emerged. The electrical properties of the substrate will seriously affect the characteristics of the digital circuit, so the performance of the board is required to be light, thin, high-density and multi-layered.

[0003] The main application areas of HDI boards are high-end fields such as mobile phones, computers, systems, system backplanes and automotive products. In order to better meet the requirements of the downstream market, the glass fiber cloth industry urgently needs to develop 1080 and 106 specifications of HDI ultra-thin board cloth that is lighter and thinner than the 7628 and 2116 thick cloth series, has higher electrical insulation performance, and can be laminated in larger quantities. Compared with the 9μm G series yarn, the 5μm D450 and D900 yarns used in the 1080 and 106 ultra-thin cloths are finer and have higher requirements for the production process. Single fibers are more likely to be broken during the drawing and twisting process, and their production efficiency has not been improved. In view of the above performance characteristics of the yarn, the wetting agent used to coat the production of D450 and D900 yarns needs to have better bundling, coating and lubricity than the G75 wetting agent to achieve the purpose of reducing the yarn hairiness; at the same time, the yarn needs to be made softer and more uniform to improve its weaving performance.

[0004] At present, the sizing agent used in the industry for coating and producing D series yarn products is still mainly based on the low-temperature system. This system not only has high modified starch cost, but also high consumption of sizing agent per ton of yarn. The utilization rate of the sizing agent is low during the wire drawing and coating process. Nearly half of the sizing agent will be thrown away, and only a small part of the sizing agent can be effectively adsorbed on the yarn bundle. At the same time, the production process requirements of D450 and D900 yarns are very strict. Not only does it require the production environment to maintain constant temperature and humidity, but also the wire drawing and twisting tension should not be too large, the production speed is slow, and the production efficiency is low. During the weaving process, D450 and D900 yarns produced by coating with low-temperature sizing agents will have a large amount of powder falling, which is easy to block the main and auxiliary nozzles of the weaving and scale on the weaving reed, resulting in the appearance of loose yarns in the weaving, and the production efficiency will also be affected. If the existing high-temperature system sizing agent is directly used to produce yarn, its stiffness will be improved. Although it is not easy to shed powder, it will cause the weft yarn to bend and the cloth surface to be uneven during weaving; at the same time, the weaving shaft will have problems such as loose warp and warp hair, so it is also not conducive to production and use.

[0005] In summary, there is an urgent need to develop a high-temperature system sizing agent to overcome the current problems of poor wear resistance of D450 and D900 yarns, harsh production environment requirements, high powder shedding, low production efficiency and many defects on the fabric surface. Summary of the invention

[0006] The purpose of this application is to provide a high-temperature starch-type sizing agent for D450 and D900 electronic-grade glass fiber yarns in order to solve the problems mentioned above. The sizing agent can be applied to produce D450 and D900 electronic-grade glass fiber yarns, which can solve the problems of high sizing agent consumption, high hairiness, poor wear resistance, and demanding process requirements in the production process. It can increase the interface bonding ability with the yarn while improving the bundling and wear resistance of the yarn. The D450 and D900 yarns produced by the sizing agent have excellent weaving performance, and the woven electronic cloth products are not prone to defects, and the cloth surface is thin and light, which meets the requirements of post-processing.

[0007] According to one aspect of the present application, a high-temperature starch-type sizing agent for electronic-grade glass fiber electronic yarn is provided, wherein the sizing agent is an aqueous solution of an effective ingredient, wherein the solid content of the sizing agent is 5.19-10.76%, wherein the effective ingredient comprises starch, grease, a pretreatment agent, an antistatic agent and ammonia water; the pretreatment agent comprises a pretreatment agent A and a pretreatment agent B; the solid mass of each effective ingredient of the sizing agent is expressed as a percentage of the total solid mass of the sizing agent as follows:

[0008]

[0009] The starch is a mixture of high-amylose corn starch, acrylamide grafted modified starch and acetyl modified starch, and the mass ratio of the high-amylose corn starch, acrylamide grafted modified starch and acetyl modified starch is 1:1:1 to 5:2:1.

[0010] The solid content of the impregnant is 5.69-10.28%, and the percentage of the solid mass of each effective component of the impregnant to the total solid mass of the impregnant is expressed as follows:

[0011]

[0012] The starch is a mixture of high-amylose corn starch, acrylamide grafted modified starch and acetyl modified starch, and the mass ratio of the high-amylose corn starch, acrylamide grafted modified starch and acetyl modified starch is 1:1:1 to 4:2:1.

[0013] The high-amylose content of the high-amylose corn starch is 40-65%; the substitution degree of the acrylamide grafted modified starch is 0.02-0.20%, and the substitution degree of the acetyl modified starch is 0.06-0.10%.

[0014] The oil is a mixed oil of hydrogenated modified soybean phosphate oil and aqueous paraffin oil or a mixed oil of hydrogenated peanut oil and aqueous paraffin oil.

[0015] The paraffin content of the aqueous paraffin oil is 60-85%, and the melting point is 40-50° C.; and the percentage of the aqueous paraffin oil in the total mass of the mixed oil is 13-24%.

[0016] Wherein, the emulsifier is at least one of polyurethane, N-dodecylmethylamine and polyvinyl alcohol.

[0017] Wherein, the pretreatment agent A includes glycerol and / or polyethylene glycol; the pretreatment agent B includes at least one of decyl glycidyl ether, glyceryl tri(1,2-epoxy)propyl ether, and higher unsaturated fatty acid glyceride.

[0018] Wherein, the antistatic agent includes at least one of alkyl dihydroxyethyl ammonium ethyl salt, ethoxy lauramide, and glyceryl stearate.

[0019] The starch needs to be ground by an ultrafine grinder, and the grinding requirement is that the passing rate of a 50-mesh sieve is greater than 99.0%.

[0020] The functions and contents of the components in the high temperature starch type sizing agent for electronic grade glass fiber electronic yarn of this application are described as follows:

[0021] The starch of the present application is a mixture of high-amylose corn starch, acrylamide grafted modified starch and acetyl modified starch. High-amylose corn starch has a good film-forming effect and can form a tough starch film with relatively stable mechanical properties under high relative humidity, but the degree of gelatinization is not high, the starch ages quickly, and the molecular agglomeration speed is fast; although the acrylamide grafted modified starch has a poor film-forming effect, the starch is easy to gelatinize, which can make up for the shortcomings of poor stability of high-amylose starch, reduce the retrogradation phenomenon of the slurry, and can improve the dispersibility of the starch slurry in the emulsion and improve the uniformity of the wetting agent coating; the acetyl modified starch has a high degree of gelatinization, which can increase the gel state of the starch slurry, so that the tensile strength of the starch film is improved, the coating of the yarn is good, and the wear resistance of the yarn can be improved. The experiment found that the use of the three starches in combination can improve the coating of the starch on the yarn, and the formed starch film is not easy to be damaged by friction. The smoothness of the yarn is increased during processing and use, and the hair caused by mechanical wear is prevented. Furthermore, the present application regulates the performance of the wetting agent by controlling the mass ratio of the three starches, wherein the mass ratio of high-amylose corn starch, acrylamide grafted modified starch and acetyl modified starch is 1:1:1 to 5:2:1, preferably 1:1:1 to 4:2:1. Experiments have found that if too much high-amylose starch is used, the yarn will easily fall off during use, the starch slurry will easily regenerate, and the shelf life of the wetting agent will be shortened; too little use will cause the yarn to be soft and the consumption of the wetting agent to increase. In the present application, the acrylamide grafted modified starch and the acetyl modified starch should be mixed and used in a mass ratio of 1:1 to 2:1. With this definition, the acrylamide grafted modified starch and the acetyl modified starch will complement each other in function, improve the film-forming effect of the starch, and make the starch film less likely to be damaged by friction. Among them, the proportion of acrylamide grafted modified starch can be appropriately increased to achieve the effect of reducing the slurry regeneration phenomenon; acetyl modified starch should not be added too much. If too much acetyl modified starch is added, the yarn will become sticky, which is not conducive to subsequent production and use.

[0022] In addition, the amount of starch used in this application needs to be controlled within a certain range. If too much is added, the wetting agent cannot be fully coated on the yarn, the utilization rate of the wetting agent is low, and most of it is wasted. Increasing the amount of starch used alone does not increase the bonding effect of the wetting agent, and the powder shedding of the yarn increases during the weaving process, which is not conducive to production and use; if the amount is too little, the smoothness of the yarn will be reduced, which is also not conducive to production and use. Therefore, the solid mass of starch in this application is controlled to be 3.4-7.0% of the total solid mass of the wetting agent, preferably 3.80-7.0%, and more preferably 3.9-6.5%.

[0023] The present application controls the amylose content in the high amylose corn starch to be 40-65%, preferably 55-60%. If the amylose content of the high amylose corn starch is too high, the stability of the impregnating agent will be poor, the starch will not be easy to gelatinize, and the impregnating agent will be easy to delaminate; if the amylose content is too low, the bundling effect cannot be achieved. At the same time, the degree of substitution of the acrylamide grafted modified starch and the acetyl modified starch of the present application needs to be controlled within an appropriate range. If the degree of substitution is too low, the modification is not thorough, the reaction conversion rate will be low, and the amount of unmodified starch will be increased, which will not play the role of modified starch, resulting in a decrease in the gelatinization degree of the starch slurry; although a high degree of substitution can also play a role, the production cost will increase. The degree of substitution of the acrylamide grafted modified starch described in the present application is 0.02-0.20%, and the degree of substitution of the acetyl modified starch is 0.06-0.10%. Preferably, the degree of substitution of the acrylamide grafted modified starch is 0.05-0.15%, and the degree of substitution of the acetyl modified starch is 0.08-0.10%.

[0024] The use of a pretreatment agent to pretreat the starch slurry is a key point of this application. If the starch slurry is not pretreated and directly cooked, the binding ability of the impregnant film and the glass fiber surface will be reduced, and powder falling will also increase. The pretreatment agent described in this application can react with the active groups of starch during the cooking process to improve the binding ability between starch molecules and between starch and the glass fiber surface, and improve the penetration ability. The treated impregnant can effectively reduce the brittleness of the starch film and the adhesion between the raw silk and the winding tube layer, and can improve the wrapping effect of the impregnant on the glass fiber yarn. D450 and D900 are 5μm glass fiber yarns, and single fibers are easy to break and difficult to gather together. In the wire drawing process, all the tows need to be gathered together. If the impregnant and the tows cannot be combined and wrapped well, they will contact with process accessories to produce hairy fibers.

[0025] The pretreatment agent described in the present application is a mixture of pretreatment agent A and pretreatment agent B. Pretreatment agent A can soften the starch film and improve the plasticity; pretreatment agent B can be combined with starch and glass fiber in the form of chemical bonds, which can improve the penetration ability of the sizing agent and help to improve the yarn strength. Preferably, the pretreatment agent A is glycerol or / and polyethylene glycol; the pretreatment agent B is at least one of decyl glycidyl ether, glyceryl tri(1,2-epoxy)propyl ether, and high-grade unsaturated fatty acid glyceride. At the same time, the amount of pretreatment agent A and pretreatment agent B needs to be controlled within a suitable range; experiments have found that if the amount of pretreatment agent A is too much, the strength of the film will decrease, and then it will break, so that it cannot play the role of coating the glass fiber yarn; if the amount is too little, the wear resistance of the yarn will deteriorate and the hairiness will increase. If the amount of pretreatment agent B is too much, it will cause the yarn to be laminated and difficult to unwind when the original silk is twisted; if the amount is too little, the desired effect cannot be achieved. Therefore, the present application controls the dosage (solid mass) of pretreatment agent A to be 0.15-0.40% of the total solid mass of the wetting agent, preferably 0.20-0.40%, and more preferably 0.25-0.30%; the solid mass of pretreatment agent B to be 0.30-0.50% of the total solid mass of the wetting agent, preferably 0.30-0.46%, and more preferably 0.30-0.40%.

[0026] Grease is a bridge for starch to adhere to glass fiber, and can also dissolve other components of the sizing agent in the water-oil emulsion. The grease described in the present application is preferably a mixture of hydrogenated modified soybean phosphate grease and aqueous paraffin oil or a mixture of hydrogenated peanut oil and aqueous paraffin oil, and the aqueous paraffin oil accounts for 13-24% of the total mass of the mixed grease.

[0027] The use of water-based paraffin oil is another key point of this application. Paraffin oil can provide a certain degree of clustering, increase the lubrication effect, make the broken hair smooth, and wrap it under the film. Compared with hydrogenated vegetable oil, the grey cloth is easy to desize after simmering after adding paraffin oil. Among them, the paraffin content in the water-based paraffin oil is 60-85%, the melting point is 40-50°C, and the melting point needs to be dissolved in hot water. After dissolving, it is not easy to re-condense into blocks.

[0028] The main function of the emulsifier is to emulsify hydrogenated oils and fats. The emulsifier described in the present application is preferably at least one of polyurethane, N-dodecylmethylamine and polyvinyl alcohol. Both polyurethane and polyvinyl alcohol can provide good emulsification effects. If N-dodecylmethylamine is added at the same time, the oil can be better dispersed and the emulsification effect can be improved. The amount of emulsifier used needs to match the amount of oil. Too little emulsification will result in insufficient emulsification; too much will result in waste. The present application controls the percentage of the solid mass of the emulsifier to the total solid mass of the wetting agent to be 0.05-0.10%, preferably 0.06-0.08%.

[0029] For yarns with thin single fiber diameters of D450 and D900, it is easy to generate electricity through friction with air and equipment during processing and use, and the requirements for temperature and humidity are relatively strict. Therefore, a certain amount of antistatic agent needs to be added to the sizing agent. In the present application, the antistatic agent is preferably at least one of alkyl dihydroxyethyl ammonium ethyl salt, ethoxy lauramide, and glyceryl stearate. If the amount of antistatic agent added is too small, it will not have the effect of removing static electricity, and if the amount added is too much, the yarn will appear to be scattered and soft. The present application controls the solid mass of the antistatic agent to a percentage of 0.17-0.40% of the total solid mass of the sizing agent, preferably 0.21-0.36%, and more preferably 0.26-0.33%.

[0030] In the present application, ammonia water can adjust the pH value of the wetting agent to make the pH value of the wetting agent neutral or weakly acidic, thereby improving the stability of the wetting agent.

[0031] In the present application, water functions as the dispersed phase of the components in the wetting agent, and is preferably deionized water.

[0032] It should be noted that, in the present application, for the effective components in the form of emulsion, the solid mass refers to the mass of the remaining part after the emulsion is dried and water is removed under certain conditions.

[0033] According to a second aspect of the present application, a method for preparing the high-temperature starch-type sizing agent for electronic-grade glass fiber yarn is provided, which specifically comprises the following steps:

[0034] Preparation of starch slurry: Mix the three starches according to the mass ratio, add water which accounts for 2-5% of the total mass of the wetting agent, and process it to the required fineness through an ultra-fine grinder; add the crushed starch and pretreatment agent into warm water which accounts for 10-20% of the total mass of the wetting agent, stir and disperse evenly, and then steam through a high-pressure reactor. After steaming, mix it with water at room temperature in equal proportions, cool it down and prepare it into starch slurry;

[0035] Preparation of emulsion: Add grease to 5-10% hot water of the total mass of the impregnant to melt, mix with the emulsifier after melting and emulsify and disperse to the required particle size;

[0036] Preparation of antistatic agent solution: dissolve the antistatic agent in room temperature water with a concentration of 5-10% of the total mass of the wetting agent, and stir until uniform;

[0037] Preparation of the wetting agent: Mix the prepared emulsion, antistatic agent solution and starch slurry, add the remaining water, and finally add ammonia water.

[0038] It should be noted that in the above operations, the ultrafine grinding process of starch should be configured before high-temperature cooking of starch, and the other steps are configured in no particular order.

[0039] Preferably, in the starch slurry preparation step, the pulverized starch and the pretreatment agent are put into water at a temperature of 15 to 30°C.

[0040] Preferably, in the step of preparing the starch slurry, the cooking flow rate is 2000-3000 kg / h, and the cooking is performed by a multi-tubular high-pressure reactor, the cooking temperature is set to 110-130°C, and the cooking pressure is set to 2-5 kgf.cm 2 .

[0041] Preferably, in the starch slurry preparation step, the starch liquid after cooking is mixed with normal temperature water with a flow rate of 2000-3000 kg / h in a mass ratio of 1:1 and cooled to prepare the starch slurry.

[0042] Preferably, in the step of preparing the emulsion, the hot water temperature is controlled at 65-75° C., and the emulsification dispersion is carried out using a high-low double-blade high-speed disperser. The particle size needs to be tested after emulsification, and the dispersion is stopped after passing the test.

[0043] Preferably, the particle size of the dispersed emulsion is required to be controlled within the range of 2 to 5 μm.

[0044] Preferably, in the antistatic agent preparation step, the room temperature water is controlled at 15-30°C.

[0045] Among them, the practice of crushing starch into smaller fineness is a key point of this application. The fineness of starch will affect the adhesion of the wetting agent to the raw silk. The fineness of starch raw materials is generally 100-150 mesh. For D450 and D900, starch particles with smaller fineness can make the configured wetting agent easier to adhere to the surface of glass fiber, with higher coverage and more uniformity. However, larger starch particles will make the surface of glass fiber rougher, which is not conducive to uniform coating of yarn surface. When the pass rate of 50 mesh screen is greater than 99.0%, the uniformity of the wetting agent is better and the consumption of wetting agent will also be reduced.

[0046] The method of using pretreatment liquid to pretreat starch slurry before cooking is another key point of this application. During the high-temperature cooking process, the pretreatment agent will react and combine with the active groups of the two modified starches, improve the binding ability between starch molecules and between starch molecules and glass fibers, improve the plasticity and permeability of the impregnant film, wrap broken yarns caused by friction, reduce the generation of hairiness, and at the same time improve the binding force between starch molecules and the surface of glass fibers, making the yarn less likely to fall off during the production process.

[0047] According to a third aspect of the present application, there are provided D450 and D900 electronic grade glass fiber products produced by coating the aforementioned electronic grade glass fiber yarn with a high temperature starch type sizing agent.

[0048] According to a fourth aspect of the present application, there is provided application of the aforementioned electronic-grade glass fiber product in the field of digital power.

[0049] The present invention improves the film-forming property of the sizing agent and increases the bonding ability of the sizing agent with the glass fiber, and utilizes the sizing agent to improve the bundling property and wear resistance of the yarn. The yarn produced by using the sizing agent has excellent weaving performance and is not prone to defects. DETAILED DESCRIPTION

[0050] In order to make the purpose, technical solutions and advantages of the present application clearer, the technical solutions of the present application will be clearly and completely described below in conjunction with the specific embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present application. It should be noted that the embodiments in the present application and the features in the embodiments can be combined with each other arbitrarily without conflict.

[0051] The embodiments in the present application and the components and features in the embodiments can be arbitrarily combined with each other. The preferred examples are only embodiments and do not include all. All combinations of components involved in the present application belong to the protection scope of the present application.

[0052] Preferred example 1:

[0053] The high-temperature starch-type sizing agent for electronic-grade glass fiber yarn according to the present application comprises effective components and water, and the solid content of the sizing agent is 5.19-10.76%, wherein the effective components comprise starch, grease, emulsifier, pretreatment agent, antistatic agent and ammonia water; the pretreatment agent comprises pretreatment agent A and pretreatment agent B; the solid mass of each effective component of the sizing agent is expressed as a percentage of the total solid mass of the sizing agent as follows:

[0054]

[0055] The starch is a mixture of high-amylose corn starch, acrylamide grafted modified starch and acetyl modified starch, and the mass ratio of the high-amylose corn starch, acrylamide grafted modified starch and acetyl modified starch is 1:1:1 to 5:2:1; the pretreatment agent A is glycerol and / or polyethylene glycol; the pretreatment agent B is at least one of decyl glycidyl ether, glycerol tri(1,2-epoxy)propyl ether and higher unsaturated fatty acid glyceride.

[0056] Preferred Example 2

[0057] The high-temperature starch-type sizing agent for electronic-grade glass fiber yarn according to the present application comprises effective components and water, and the solid content of the sizing agent is 5.19-10.76%; wherein the effective components comprise starch, grease, emulsifier, pretreatment agent, antistatic agent and ammonia water, and the pretreatment agent comprises pretreatment agent A and pretreatment agent B; the solid mass of each effective component of the sizing agent is expressed as a percentage of the total solid mass of the sizing agent as follows:

[0058]

[0059]

[0060] The starch is a mixture of high-amylose corn starch, acrylamide grafted modified starch and acetyl modified starch, and the mass ratio of the high-amylose corn starch, acrylamide grafted modified starch and acetyl modified starch is 1:1:1-4:2:1; and the high-amylose content of the high-amylose corn starch is 40-65%, the degree of substitution of the acrylamide grafted modified starch is 0.02-0.20%, and the degree of substitution of the acetyl modified starch is 0.06-0.10%.

[0061] Preferred Example 3

[0062] The high-temperature starch-type sizing agent for electronic-grade glass fiber yarn according to the present application comprises effective components and water, and the solid content of the sizing agent is 5.19-10.76%; wherein the effective components comprise starch, grease, emulsifier, pretreatment agent, antistatic agent and ammonia water, and the pretreatment agent comprises pretreatment agent A and pretreatment agent B; the solid mass of each effective component of the sizing agent is expressed as a percentage of the total solid mass of the sizing agent as follows:

[0063]

[0064] The starch is a mixture of high-amylose corn starch, acrylamide grafted modified starch and acetyl modified starch, wherein the mass ratio of high-amylose corn starch, acrylamide grafted modified starch and acetyl modified starch is 1:1:1-4:2:1; the high-amylose corn starch has an amylose content of 55-60%, the degree of substitution of acrylamide grafted modified starch is 0.05-0.15%, and the degree of substitution of acetyl modified starch is 0.08-0.10%;

[0065] The oil is a mixture of hydrogenated modified soybean phosphate oil and water-based paraffin oil, and the water-based paraffin oil accounts for 13-24% of the total mass of the mixed oil;

[0066] The pretreatment agent A is glycerol and / or polyethylene glycol; the pretreatment agent B is at least one of decyl glycidyl ether, glyceryl tri(1,2-epoxy)propyl ether, and higher unsaturated fatty acid glyceride.

[0067] Preferred Example 4

[0068] The high-temperature starch-type sizing agent for electronic-grade glass fiber yarn according to the present application comprises effective components and water, and the solid content of the sizing agent is 5.69-10.28%; wherein the effective components comprise starch, grease, emulsifier, pretreatment agent, antistatic agent and ammonia water, and the pretreatment agent comprises pretreatment agent A and pretreatment agent B; the solid mass of each effective component of the sizing agent is expressed as a percentage of the total solid mass of the sizing agent as follows:

[0069]

[0070] The starch is a mixture of high-amylose corn starch, acrylamide grafted modified starch and acetyl modified starch, the mass ratio of high-amylose corn starch, acrylamide grafted modified starch and acetyl modified starch is 1:1:1-5:2:1; the high-amylose content of high-amylose corn starch is 40-65%, the degree of substitution of acrylamide grafted modified starch is 0.02-0.20%, and the degree of substitution of acetyl modified starch is 0.06-0.10%;

[0071] The pretreatment agent A is glycerol and / or polyethylene glycol; the pretreatment agent B is at least one of decyl glycidyl ether, glyceryl tri(1,2-epoxy)propyl ether, and higher unsaturated fatty acid glyceride.

[0072] Preferred Example 5

[0073] The high-temperature starch-type sizing agent for electronic-grade glass fiber yarn according to the present application comprises effective components and water, and the solid content of the sizing agent is 5.69-10.28%; wherein the effective components comprise starch, grease, emulsifier, pretreatment agent, antistatic agent and ammonia water, and the pretreatment agent comprises pretreatment agent A and pretreatment agent B; the solid mass of each effective component of the sizing agent is expressed as a percentage of the total solid mass of the sizing agent as follows:

[0074]

[0075] The starch is a mixture of high-amylose corn starch, acrylamide grafted modified starch and acetyl modified starch, the mass ratio of high-amylose corn starch, acrylamide grafted modified starch and acetyl modified starch is 1:1:1-4:2:1; the high-amylose content of the high-amylose corn starch is 40-65%, the degree of substitution of the acrylamide grafted modified starch is 0.02-0.20%, and the degree of substitution of the acetyl modified starch is 0.06-0.10%;

[0076] The oil is a mixture of hydrogenated modified soybean phosphate oil and water-based paraffin oil, and the water-based paraffin oil accounts for 13-24% of the total mass of the mixed oil;

[0077] The pretreatment agent A is glycerol and / or polyethylene glycol; the pretreatment agent B is at least one of decyl glycidyl ether, glyceryl tri(1,2-epoxy)propyl ether, and higher unsaturated fatty acid glyceride.

[0078] Preferred Example 6

[0079] The high-temperature starch-type sizing agent for electronic-grade glass fiber yarn according to the present application comprises effective components and water, and the solid content of the sizing agent is 5.69-10.28%; wherein the effective components comprise starch, grease, emulsifier, pretreatment agent, antistatic agent and ammonia water, and the pretreatment agent comprises pretreatment agent A and pretreatment agent B; the solid mass of each effective component of the sizing agent is expressed as a percentage of the total solid mass of the sizing agent as follows:

[0080]

[0081]

[0082] The starch is a mixture of high-amylose corn starch, acrylamide grafted modified starch and acetyl modified starch, the mass ratio of the high-amylose corn starch, acrylamide grafted modified starch and acetyl modified starch is 1:1:1-5:2:1; the high-amylose content of the high-amylose corn starch is 55-60%, the degree of substitution of the acrylamide grafted modified starch is 0.05-0.15%, and the degree of substitution of the acetyl modified starch is 0.08-0.10%;

[0083] The pretreatment agent A is glycerol and / or polyethylene glycol; the pretreatment agent B is at least one of decyl glycidyl ether, glyceryl tri(1,2-epoxy)propyl ether, and higher unsaturated fatty acid glyceride.

[0084] Preferred Example 7

[0085] The high-temperature starch-type sizing agent for electronic-grade glass fiber yarn according to the present application comprises effective components and water, and the solid content of the sizing agent is 6.29-9.36%; wherein the effective components comprise starch, grease, emulsifier, pretreatment agent, antistatic agent and ammonia water, and the pretreatment agent comprises pretreatment agent A and pretreatment agent B; the solid mass of each effective component of the sizing agent is expressed as a percentage of the total solid mass of the sizing agent as follows:

[0086]

[0087] The starch is a mixture of high-amylose corn starch, acrylamide grafted modified starch and acetyl modified starch, the mass ratio of the high-amylose corn starch, acrylamide grafted modified starch and acetyl modified starch is 1:1:1-4:2:1; the amylose content of the high-amylose corn starch is 55-60%, the degree of substitution of the acrylamide grafted modified starch is 0.05-0.15%, and the degree of substitution of the acetyl modified starch is 0.08-0.10%;

[0088] The oil is a mixture of hydrogenated modified soybean phosphate oil and water-based paraffin oil, and the water-based paraffin oil accounts for 13-24% of the total mass of the mixed oil;

[0089] The pretreatment agent A is glycerol and / or polyethylene glycol; the pretreatment agent B is at least one of decyl glycidyl ether, glyceryl tri(1,2-epoxy)propyl ether, and higher unsaturated fatty acid glyceride.

[0090] The preparation method of each of the above preferred examples of the wetting agent comprises the following steps:

[0091] Preparation of starch slurry: after three kinds of starch are mixed according to the mass ratio, water of 2-5% of the total mass of the impregnating agent is added, and the mixture is processed to the required fineness by an ultrafine grinder; after the pulverized starch and pretreatment agent are added to water of 15-30° C. of 10-20% of the total mass of the impregnating agent, the mixture is stirred and dispersed uniformly, and then the mixture is steamed in a high-pressure reactor; after the steaming is completed, the mixture is mixed with normal temperature water of 2000-3000 kg / h in a mass ratio of 1:1, and the mixture is cooled and prepared into starch slurry; the steaming flow rate is 2000-3000 kg / h, and the mixture is steamed in a multi-tube high-pressure reactor, the steaming temperature is set to 110-130° C., and the steaming pressure is set to 2-5 kgf.cm 2 ;

[0092] Preparation of emulsion: Add grease to 65-75°C water which is 5-10% of the total mass of the impregnating agent to melt, and after melting, mix with the emulsifier and emulsify and disperse to a particle size of 2-5 μm;

[0093] Preparation of antistatic agent solution: dissolve the antistatic agent in 15-30°C water, which is 5-10% of the total mass of the wetting agent, and stir until it is uniform;

[0094] Preparation of the wetting agent: Mix the prepared emulsion, antistatic agent solution and starch slurry, add the remaining water, and finally add ammonia water.

[0095] In order to better explain the technical solution of the present application, some specific embodiments 1 to 12 of the high-temperature starch-type sizing agent for electronic-grade glass fiber yarn of the present application are listed below, wherein the specific formula of each component of the sizing agent of embodiments 1 to 12 is shown in Table 1.

[0096] Table 1 Wetting agent formulations for each embodiment

[0097]

[0098]

[0099] Table 1 (Continued) Wetting agent formulations for various examples

[0100]

[0101] Among them, in Examples 1 to 12, the high amylose content of high amylose corn starch is 40 to 65%. The degree of substitution of acrylamide grafted modified starch is 0.02 to 0.20%, and the degree of substitution of acetyl modified starch is 0.06 to 0.10%. The preparation method of the wetting agent in each embodiment is the same as the preparation method of the preferred example wetting agent. In order to further reflect the beneficial effects of the present application, the performance of D450 and D900 products produced by currently commonly used wetting agents are selected as comparative examples and compared with the product performance of the specific embodiments of the present application.

[0102] Comparative Example 1:

[0103] The impregnating agent contains active ingredients and water, with a solid content of 6.0%. The percentage of the solid mass of each active component to the total solid mass of the impregnating agent is expressed as follows:

[0104]

[0105] The degree of substitution of the esterified modified amylopectin is 0.15-0.20%, and the degree of substitution of the etherified modified amylopectin is 0.10-0.15%.

[0106] Comparative Example 2:

[0107] The impregnating agent contains active ingredients and water, with a solid content of 6.4%. The percentage of the solid mass of each active component to the total solid mass of the impregnating agent is expressed as follows:

[0108]

[0109] The degree of substitution of the hydroxyethyl modified amylopectin is 0.05-0.15%, and the degree of substitution of the etherified modified amylopectin is 0.10-0.20%.

[0110] Wherein, the preparation method of comparative examples 1 to 2 comprises the following steps:

[0111] 1. The concentration of starch is controlled at 10-20% by mass. The starch is added into normal temperature water according to the mass ratio, stirred and dispersed evenly, and then heated to 85-99°C and steamed for 60 minutes. After steaming, 10-20% of the mass ratio of the wetting agent is slowly added into normal temperature water to cool down.

[0112] 2. Add grease and emulsifier, add hot water with a mass ratio of 10-20% of the wetting agent, control the hot water temperature to 60-70°C, emulsify for 30 minutes by high-speed stirring, then add antistatic agent and other additives to the emulsion and stir for 30-60 minutes to prepare an emulsion;

[0113] 3. Add the prepared emulsion into the starch slurry, add the remaining water, and finally add ammonia water and stir evenly.

[0114] Comparative Example 3:

[0115] The impregnating agent contains active ingredients and water, with a solid content of 8.72%. The percentage of the solid mass of each active component to the total solid mass of the impregnating agent is expressed as follows:

[0116] Starch: high amylose corn starch 0.8%, acrylamide grafted modified starch 1.5%, acetyl modified starch 3.2%;

[0117] Oil: hydrogenated modified soybean phosphate oil 1.7%, water-based paraffin oil 0.4%;

[0118] Emulsifier: polyurethane 0.06%;

[0119] Pretreatment agent A: 0.16% glycerol, 0.04% polyethylene glycol;

[0120] Pretreatment agent B: 0.13% decyl glycidyl ether, 0.1% glycerol tri(1,2-epoxy)propyl ether, 0.1% higher unsaturated fatty acid glyceride;

[0121] Antistatic agent: 0.1% alkyl dihydroxyethyl ammonium ethyl salt, 0.2% polydimethylsiloxane;

[0122] Ammonia 0.05%;

[0123] The preparation method refers to the preparation method of the wetting agent in the example.

[0124] Comparative Example 4:

[0125] The formulation of Comparative Example 4 has the same components as those of Example 5 except that the pretreatment agent is not included, and the solid content is 7.6%.

[0126] The preparation method of Comparative Example 4 does not include the step of cooking the starch slurry with a pretreatment agent, and does not include the step of processing the starch with an ultrafine grinder. The remaining processes are the same as those of Comparative Example 3.

[0127] Production performance testing:

[0128] In this application, the sizing agents of Examples 1 to 12 and Comparative Examples 1 to 4 were tested for production. D450 and D900 differed only in the number of pulls and the number of yarns. The rest of the production processes were the same. Each example produced 1,000 bobbins. The process parameters are shown in Table 2.

[0129] Table 2 Production process parameters

[0130] Wire drawing head speed (r / min) 3400~3600 Oiling line speed (m / min) 16~20 Wetting agent use temperature (℃) 55~65 Twist(twist / m) 32~38 Twisting machine spindle speed (rpm / min) 2000~4500 Twisting temperature(℃) 20~30 Twisting humidity (%) 35~60 Loom speed (rpm / min) 600~750

[0131] Among them, in order to better illustrate the effect of the present application, the comparative example and the embodiment have the same production process parameters. The yarn test method adopts GB / T 7690 "Reinforced Material Yarn Test Method", GB / T 9914 "Reinforced Product Test Method", FZ / T01058-1999 "Yarn Abrasion Test Method Reciprocating Grinding Roller Method", and the woven cloth powder falling amount is compared with the data collected for one day by placing a closed square box in the yarn beating path, and the test results are shown in Table 3.

[0132] Table 3 Test results of embodiments and comparative examples

[0133]

[0134] Table 3 (continued) Test results of embodiments and comparative examples

[0135]

[0136]

[0137] The performance test results in Table 3 show that the D450 and D900 electronic-grade glass fiber yarns produced by the high-temperature starch-type sizing agent for electronic-grade glass fiber yarns of Examples 1 to 12 of the present application have an oil content of 1.25 to 1.36% and a water content of 0.02 to 0.06%, and a twist of 32.2 to 35.8 twists / m. In terms of the performance of the embodiment, the breakage rate of the tube yarn is 0.9 to 1.9%, which is significantly lower than that of Comparative Examples 1 to 4. The hairiness rate of the tube yarn of the embodiment is between 0.3 and 1.3%, and the hairiness of the glass fiber yarn is significantly reduced compared with Comparative Examples 1 to 4. The wear resistance times of the embodiment of the present application are 56 to 70 times, which is much higher than the wear resistance times of the comparative example, indicating that the yarn of the embodiment of the present application is more wear-resistant. The powder shedding amount of the woven fabric of the embodiment of the present application is 11.5 to 14.5 mg / d, and the powder shedding amount is significantly less than that of each comparative example. In addition, the embodiment is not easy to scale and cause defects during weaving, and the number of defects on the cloth surface is 11.8 to 21.0 per 10,000 meters, which is nearly half the number of defects in the weaving compared with Comparative Examples 1 to 4, so it is more suitable for weaving production applications than the comparative examples. As can be seen from the above, the electronic-grade glass fiber yarn produced by the high-temperature starch-type sizing agent for D450 and D900 electronic-grade glass fiber yarn of the present application has low hairiness and broken ends, the yarn is uniform and soft, the weaving has less powder shedding, and the weaving has fewer defects.

[0138] In summary, the high-temperature starch-type sizing agent formula and configuration process for D450 and D900 electronic-grade glass fiber yarns provided by this application are scientific and reasonable, and the components in the formula cooperate with each other to solve the problems of high hairiness, poor yarn wear resistance, high powder shedding and high fabric defects in the D450 and D900 low-temperature system formulas. Therefore, this application is of great significance in upgrading product quality.

[0139] Finally, it should be noted that in this article, the terms "include", "comprises" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device that includes a series of elements includes not only those elements, but also includes other elements that are not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of more restrictions, an element defined by the sentence "comprises a ..." does not exclude the presence of other identical elements in the process, method, article or device that includes the element.

[0140] The above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them. Although the present application is described in detail with reference to the above embodiments, a person skilled in the art should understand that the technical solutions described in the above embodiments can still be modified, or some of the technical features can be replaced by equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the spirit and scope of the technical solutions of the embodiments of the present application.

Claims

1. A high-temperature starch-type sizing agent for electronic-grade glass fiber yarn, the sizing agent being an aqueous solution of an active ingredient, characterized in that: The solid content of the sizing agent is 5.19-10.76%, wherein the effective components include starch, oil, emulsifier, pretreatment agent, antistatic agent and ammonia water; the pretreatment agent includes pretreatment agent A and pretreatment agent B; the percentage of the solid mass of each effective component of the sizing agent to the total solid mass of the sizing agent is expressed as follows: The starch is a mixture of high-amylose corn starch, acrylamide grafted modified starch and acetyl modified starch, and the mass ratio of the high-amylose corn starch, acrylamide grafted modified starch and acetyl modified starch is 1:1:1 to 5:2:1; The high amylose content of the high amylose corn starch is 40-65%; the substitution degree of the acrylamide grafted modified starch is 0.02-0.20%, and the substitution degree of the acetyl modified starch is 0.06-0.10%; The pretreatment agent A includes glycerol and / or polyethylene glycol; the pretreatment agent B includes at least one of decyl glycidyl ether, glyceryl tri(1,2-epoxy)propyl ether, and higher unsaturated fatty acid glyceride; The oil is a mixture of hydrogenated modified soybean phosphate oil and aqueous paraffin oil or a mixture of hydrogenated peanut oil and aqueous paraffin oil; The emulsifier is at least one of polyurethane, N-dodecylmethylamine and polyvinyl alcohol; The antistatic agent includes at least one of alkyl dihydroxyethyl ammonium ethyl salt, ethoxy lauramide, and glyceryl stearate.

2. The wetting agent according to claim 1, characterized in that The solid content of the impregnant is 5.69-10.28%, and the percentage of the solid mass of each effective component of the impregnant to the total solid mass of the impregnant is expressed as follows: The starch is a mixture of high-amylose corn starch, acrylamide grafted modified starch and acetyl modified starch, and the mass ratio of the high-amylose corn starch, acrylamide grafted modified starch and acetyl modified starch is 1:1:1 to 4:2:

1.

3. The wetting agent according to claim 1, characterized in that The paraffin content of the aqueous paraffin oil is 60-85%, and the melting point is 40-50° C.; and the percentage of the aqueous paraffin oil in the total mass of the mixed oil is 13-24%.

4. The wetting agent according to claim 1, characterized in that The starch needs to be ground by an ultra-fine grinder, and the grinding requirement is that the passing rate of a 50-mesh screen is greater than 99.0%.

5. The method for preparing the wetting agent according to any one of claims 1 to 3, characterized in that: The steps include: Preparation of starch slurry: Mix the three starches according to the mass ratio, add water which accounts for 2-5% of the total mass of the wetting agent, and process it to the required fineness through an ultra-fine grinder; add the crushed starch and pretreatment agent into warm water which accounts for 10-20% of the total mass of the wetting agent, stir and disperse them evenly, and then steam them through a high-pressure reactor. After steaming, mix them with normal temperature water in an equal mass ratio, cool them down and prepare them into starch slurry; Preparation of emulsion: Add grease to 5-10% of the total mass of the impregnant in hot water to melt, mix with emulsifier after melting and emulsify and disperse to the required particle size; Preparation of antistatic agent solution: dissolve the antistatic agent in room temperature water with a concentration of 5-10% of the total mass of the wetting agent, and stir until uniform; Preparation of the wetting agent: Mix the prepared emulsion, antistatic agent solution and starch slurry, add the remaining water, and finally add ammonia water.

6. D450, D900 electronic grade glass fiber yarn products produced by coating with the sizing agent according to any one of claims 1 to 3.

7. Application of the electronic-grade glass fiber yarn product as claimed in claim 6 in the field of digital power.

Citation Information

Patent Citations

  • Impregnating compound for low-twist electronic-grade glass fibers as well as preparation method and application of impregnating compound

    CN116535111A

  • Sizing agent for glass fiber containing starch acetate

    JP2003095703A

  • Sizing agent for glass fiber yarn and glass fiber yarn using the same

    JP2004115350A

Cited By

  • High-temperature starch-type impregnating compound for electronic-grade glass fiber yarn as well as preparation method and application of high-temperature starch-type impregnating compound

    CN121021011A

  • High-temperature starch type sizing agent for electronic-grade glass fiber yarn, and preparation method and application thereof

    CN121021011B